Re-evaluating the basis of clonal selection in germinal centres - Long, Z (2022)
Effective humoral responses rely on the development of high-affinity antigen-specific B cells. However, the naïve repertoire of antibodies usually shows low affinity. B cells need to improve their affinity in secondary lymphoid structures known as germinal centres (GCs) during infections, a process known as affinity maturation. In GCs, B cells undergo iterative rounds of somatic hypermutation in the dark zones (DZs) to diversify BCRs then exit cell cycle and move back to light zones (LZs) for affinity-based selection. In the LZs, it has long been considered that only selected cells could subsequently reenter cell cycle and move back to DZs, a process known as cyclic re-entry. Affinity enhancements are thought to be conferred via T cells providing help to the highest affinity LZ B cells to initiate cyclic re-entry, however, this hypothesis was never directly tested. Using fluorescent cell cycle reporter mice, we found neither T cells depletion nor MHCII deletion abolished the cyclic re-entry initiation in LZ cells and this process was not detectably restricted by general intra-GC competition. Concurrently, using BATF as a marker for recent T-B interactions, we found B cells needed to compete in order to receive T cell mediated refuelling in an affinity dependent manner. However, this process was also limited by B cells’ intrinsic ability to acquire antigens. Consistent with the observations above, cyclic re-entry LZ cells were found to be heterogeneous at their BATF levels, further confirming cyclic re-entry initiation and receiving T cell mediated refuelling are two processes regulated independently. Our data is pointing towards a less binary selection mechanism in GCs, which confers proliferative advantage to higher affinity clones while allowing low-affinity cells to mature via more complex pathways so that antibody repertoires are matured for both affinity and clonal diversity.